Cuba adrift in a postcommunist world - Gonzalez, Edward; Ronfeldt, David F. 1941- (RAND, 1992)
The Castro regime remains in the throes of its worst crisis. The failure of the right-wing Soviet coup and the subsequent dissolution of the USSR at the end of 1991 have left Cuba adrift in the world and its economy in shambles. Nevertheless, the regime is likely to survive over the short- and possibly mid-term. It possesses a strong, repressive state, while facing a weak "civil society." However, if the economic decline is not arrested, uncontrolled, potentially violent change could be detonated by disaffected elements within the regime or by an increasingly desperate populace. U.S. policy needs to discriminate carefully between a Cuba under Castro and a Cuba after Castro. It also needs to be flexible. Neither heightening U.S. pressures nor lifting the U.S. embargo are advisable at present, and both could lock U.S. policy into irreversible modes. Persisting with the established policy of containment is preferable for now, but it should be modified with a new information and communication policy to promote civil society and prepare for a Cuba after Castro.
Keywords: Außenpolitik; Politik; Wirtschaft; USA; Cuba -- Economic conditions -- 1990-; Cuba -- Foreign relations -- United States; Cuba -- Politics and government -- 1959-1990; United States -- Foreign relations -- 1993-2001; United States -- Foreign relations -- Cuba